Penerapan Reward dan Punishment di Lembaga Manajemen Infaq Surabaya - Muhamad Hidayat (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2024)
An organization has reasons to manifest the implementation of rewards and punishments, including at the Lembaga Manajemen Infaq Surabaya. The aim of this research is to explore the processes and forms of rewards and punishments. Similarly, this research utilizes a qualitative approach with data collected through observation, interviews, and documentation. In the end, the research results obtained are the rewards and punishments process including: a) enforcement of rewards and punishments in accordance with regulations, b) follow up rewards and punishments with coaching programs, c) communicate the results of confirmation related to the timing of rewards and punishments, d) evaluating the impact of rewards and punishments. Furthermore, the forms of rewards are divided into two categories, namely financial and non-financial. Meanwhile, the forms of punishment are in the form of verbal reprimands, reduction in income, transfer and demotion, as well as warning letters and termination of employment.